Teleworking for Indonesian Civil Servants: Problems and Actors - Suarlan, Suarlan (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Teleworking can become an alternative in doing the office work. This working method allows people to do their job in an unconventional way. It allows workers to work outside of the office, for example, from their homes. This method has brought both advantages and disadvantages. The advancing communication technology gives more confident that the teleworking would be more popular. However, teleworking is not quite popular in Indonesia, especially in the public sector. Although the country is still growing in terms of communication infrastructure, it seems that teleworking might less likely be chosen as a working method. Considering the nature of the government and the bureaucracy reform, this article give the preliminary arguments as to why teleworking would likely not work in Indonesian bureaucracy, thus to explain who the actors that could have capabilities to solve it.